2012
DOI: 10.1111/j.1754-4505.2012.00249.x
|View full text |Cite
|
Sign up to set email alerts
|

Schwartz–Jampel syndrome: a review of the literature and case report

Abstract: Schwartz-Jampel syndrome (SJS) is a rare autosomal recessive skeletal dysplasia associated with myotonia. The manifestations of SJS include short stature, blepharophimosis, and skeletal anomalies. The combination of skeletal and muscular abnormalities may result in oro-dental manifestations such as atypical facies, with micrognathia, microstomia, pursed lips, crossbite, cleft palate, as well as mandibular hypoplasia, the risk of dentigerous cysts, and impacted teeth. The use of general anesthesia in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 35 publications
0
17
2
Order By: Relevance
“…Schwartz–Jampel syndrome is an uncommon autosomal recessive disorder associated with mutations in the HSPG2 gene encoding perlecan, the major heparan sulfate proteoglycan of basement membranes. The presentation includes short stature, blepharophimosis (ptosis with reduced lid size), and chondrodysplasia manifesting as kyphoscoliosis, bowing of long bones, and pectus carinatum . Percussion myotonia and depressed reflexes are found on examination.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…Schwartz–Jampel syndrome is an uncommon autosomal recessive disorder associated with mutations in the HSPG2 gene encoding perlecan, the major heparan sulfate proteoglycan of basement membranes. The presentation includes short stature, blepharophimosis (ptosis with reduced lid size), and chondrodysplasia manifesting as kyphoscoliosis, bowing of long bones, and pectus carinatum . Percussion myotonia and depressed reflexes are found on examination.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…4 It has also been reported that the unilateral form of dental agenesis was more common than the bilateral version. 4,14,15 Single mandibular central incisor in mandible in has been reported and authors stated found the association with chromosome 18p. 16 Similarly, in the present case unilateral absence of central incisor was evident in both primary and permanent dentition.…”
Section: Discussionmentioning
confidence: 98%
“…Patients with the Freeman-Sheldon syndrome may have problems to ventilate their airways and be at a high risk of developing pulmonary complications 26 . Patients with the Schwartz-Jampel syndrome are at risk of developing malignant hyperthermia 45 . Similarly, in Moebius syndrome there is a risk of palatine tracheomalacia and uvula weakness leading to the loss of airway function and respiratory insufficiency 28 .…”
Section: Therapeutic Adaptations In Patients With Microstomiamentioning
confidence: 99%
“…To treat patients with microstomia, the dentist will need small rotary instruments such as dental burs with small heads and short axis 21,42,44,45 . The use of magnifying loupes to work with more precision is often helpful.…”
Section: Therapeutic Adaptations In Patients With Microstomiamentioning
confidence: 99%